Pelatihan Technological Pedagogical Content Knowledge (TPACK) Sebagai Kerangka Pengetahuan untuk Meningkatkan Kompetensi Guru - Sandra Sukmaning Adji; Dyah Aniza Kismiati; Heni Safitri; Hartinawati Hartinawati; Sugilar Sugilar; Idha Novianti; Zakirman Zakirman (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service program aims to improve the teacher competence through Technological Pedagogical Content Knowledge (TPACK) training. The targets of this service program are elementary school teachers and twenty one junior high school teachers from various schools in South Tangerang. The service instrument used was a questionnaire with questions in the form of a Likert scale, then analyzed using descriptive analysis method. The result of this service shows that almost all participants agree and strongly agree that the TPACK material is useful for improving teacher competence. According to the teachers, after participating in the TPACK training, they can open their horizons to use learning programs that can be accessed through various learning resources. They even want to explore the material about TPACK. This is because TPACK is able to integrate pedagogic, content and technology elements in learning. After participating in the TPACK training, the teachers stated that they would try to apply TPACK in their classroom learning and try to choose learning strategies according to student needs. They even want to try to find sources of material from various learning resources related to TPACK.